Clinical pharmacists in palliative care: effects on drug therapy and drug expenses Apotheker auf der Palliativstation: Auswirkung auf Arzneimitteltherapie und Therapiekosten - Wolf, Carolin; Dörje, Frank; Klein, Carsten; Ostgathe, Christoph (Schmerz, 2019)
Background: The effect of integrating clinical pharmacists in German palliative care units with regard to the quality of drug therapy and drug costs has yet not been evaluated. Objectives: This work aims to assess the number of pharmaceutical interventions (PI) and the cost-benefit ratio of a clinical pharmacist taking part in the interprofessional patient care team on an inpatient palliative care unit in Germany. Methods: The number of and underlying reasons for the pharmacist-led recommendations were recorded and analyzed over a 1-year period. In addition, the respective drugs and the acceptance rate of recommendations were assessed. To evaluate the cost-benefit ratio, the financial savings in the provision of drugs were recorded and compared with the expenses for the clinical pharmacy service. Results: A total of 245 PI were performed. Most frequently, the pharmacist advised physicians on drug choices and drug dosages. The acceptance rate was 93%. The cost savings in the provision of drugs covered 83% of the expenses for the clinical pharmacy service. Conclusion: The results indicate that the integration of a clinical pharmacist is well suited to optimizing the interprofessional treatment of distressing symptoms with a beneficial economic outcome in palliative care. Consequently, the permanent integration of a clinical pharmacist on an inpatient palliative care unit seems to be beneficial and advisable.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Cost-benefit analysis; Palliative medicine; Pharmaceutical services; Symptom control; Terminal care

Depression in palliative care - Schwartz, Jacqueline; Neukirchen, Martin; Hornemann, Beate; Gaertner, Jan; Wolf, Carolin; Thomas, Michael (Die Onkologie, 2022)
CRIS-Team WoS Importer:2022-10-14

Effect of a Multi-Dimensional and Inter-Sectoral Intervention on the Adherence of Psychiatric Patients - Pauly, Anne; Wolf, Carolin; Mayr, Andreas; Lenz, Bernd; Kornhuber, Johannes; Friedland, Kristina (PLoS ONE, 2015)
In psychiatry, hospital stays and transitions to the ambulatory sector are susceptible to major changes in drug therapy that lead to complex medication regimens and common non-adherence among psychiatric patients. A multi-dimensional and inter-sectoral intervention is hypothesized to improve the adherence of psychiatric patients to their pharmacotherapy.269 patients from a German university hospital were included in a prospective, open, clinical trial with consecutive control and intervention groups. Control patients (09/2012-03/2013) received usual care, whereas intervention patients (05/2013-12/2013) underwent a program to enhance adherence during their stay and up to three months after discharge. The program consisted of therapy simplification and individualized patient education (multi-dimensional component) during the stay and at discharge, as well as subsequent phone calls after discharge (inter-sectoral component). Adherence was measured by the "Medication Adherence Report Scale" (MARS) and the "Drug Attitude Inventory" (DAI).The improvement in the MARS score between admission and three months after discharge was 1.33 points (95% CI: 0.73-1.93) higher in the intervention group compared to controls. In addition, the DAI score improved 1.93 points (95% CI: 1.15-2.72) more for intervention patients.These two findings indicate significantly higher medication adherence following the investigated multi-dimensional and inter-sectoral program.German Clinical Trials Register DRKS00006358.
EVALuna2:5516

Pharmacist-Led Medication Reviews to Identify and Collaboratively Resolve Drug-Related Problems in Psychiatry - A Controlled, Clinical Trial - Wolf, Carolin; Pauly, Anne; Mayr, Andreas; Groemer, Teja; Lenz, Bernd; Kornhuber, Johannes; Friedland, Kristina (PLoS ONE, 2015)
This prospective, controlled trial aimed to assess the effect of pharmacist-led medication reviews on the medication safety of psychiatric inpatients by the resolution of Drug-Related Problems (DRP). Both the therapy appropriateness measured with the Medication Appropriateness Index (MAI) and the number of unsolved DRP per patient were chosen as primary outcome measures.Depending on their time of admission, 269 psychiatric patients that were admitted to a psychiatric university hospital were allocated in control (09/2012-03/2013) or intervention group (05/2013-12/2013). In both groups, DRP were identified by comprehensive medication reviews by clinical pharmacists at admission, during the hospital stay, and at discharge. In the intervention group, recommendations for identified DRP were compiled by the pharmacists and discussed with the therapeutic team. In the control group, recommendations were not provided except for serious or life threatening DRP. As a primary outcome measure, the changes in therapy appropriateness from admission to discharge as well as from admission to three months after discharge (follow-up) assessed with the MAI were compared between both groups. The second primary outcome was the number of unsolved DRP per patient after completing the study protocol. The DRP type, the relevance and the potential of drugs to cause DRP were also evaluated.The intervention led to a reduced MAI score by 1.4 points per patient (95% confidence interval [CI]: 0.8-2.0) at discharge and 1.3 points (95% CI: 0.7-1.9) at follow-up compared with controls. The number of unsolved DRP in the intervention group was 1.8 (95% CI: 1.5-2.1) less than in control.The pharmaceutical medication reviews with interdisciplinary discussion of identified DRP appears to be a worthy strategy to improve medication safety in psychiatry as reflected by less unsolved DRP per patient and an enhanced appropriateness of therapy. The promising results of this trial likely warrant further research that evaluates direct clinical outcomes and health-related costs.Deutsches Register Klinischer Studien (DRKS), DRKS00006358.
EVALuna2:5531

SOP – Darmpassagestörung in der Palliativmedizin - Ettrich, Thomas; Schönsteiner, Stefan; Mayer-Steinacker, Regine; Stilgenbauer, Stephan; Gog, Christiane; Thuss-Patience, Peter; Wolf, Carolin; Ostgathe, Christoph (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-02-16

SOP – Fatigue - Cuhls, H.; Mochamat; Mücke, M.; Jaspers, B.; Jentschke, E.; Hense, J.; Wolf, Carolin; Ostgathe, Christoph; Radbruch, L. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-03-29

SOP – Inappetenz und Kachexie - Eschbach, C.; Villalobos, M.; Wolf, Carolin; Thomas, M. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-03-29

SOP – Palliative Sedierung - Oechsle, Karin; Radbruch, Lukas; Wolf, Carolin; Ostgathe, Christoph (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-03-29

SOP – Schmerztherapie bei Palliativpatienten - Viehrig, Marén; Schlisio, Barbara; Thomas, Michael; Gärtner, Jan; Wolf, Carolin; Hense, Jörg (Die Onkologie, 2024)
SOP aus der monatlich erscheinenden Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der Arbeitsgemeinschaft (AG) Palliativmedizin der von der Deutschen Krebshilfe geförderten CCCs.<br
CRIS-Team Scopus Importer:2024-03-29

SOP – Subkutane Medikamentengabe und Infusionen in der erwachsenen Palliativmedizin - Hense, J.; Przyborek, M.; Rosenbruch, J.; Ostgathe, Christoph; Wolf, Carolin; Bogner, S. (Die Onkologie, 2024)
CRIS-Team Scopus Importer:2024-03-29

SOP – Subkutane Medikamentengabe und Infusionen in der erwachsenen Palliativmedizin Version II - Hense, J.; Przyborek, M.; Rosenbruch, J.; Ostgathe, Christoph; Wolf, Carolin (Die Onkologie, 2023)
CRIS-Team Scopus Importer:2023-09-29